Un/doing Race Rassifizierung in der Schweiz - dos Santos Pinto, Jovita; Ohene-Nyako, Pamela; Pétrémont, Mélanie-Evely; Lavanchy, Anne; Lüthi, Barbara; Purtschert, Patricia; Skenderovic, Damir (Seismo, 2022)
What is the meaning of race, racialization and racism in Switzerland and how are they related to Switzerland's colonial heritage? How has the approach to racism changed historically? What role does anti-racist activism play, especially activism by black people and people of color? By discussing such questions, the volume shows how racism is ingrained in the structures of modern societies. As the articles show, structural and everyday racism can also be found in Switzerland in various areas of society. On the one hand, this volume offers concepts and approaches to understand processes and mechanisms of racialization. The book thus creates the basis for a critical scientific reflection on racism and the use of the analytical category race in Switzerland.